Ovarian maturation stages of wild and captive mud crab, Scylla olivacea fed with two diets - Azmie Ghazali,; Noordiyana Mat Noordin,; Ambok Bolong Abol-Munafi,; Mohamad N. Azra,; Mhd Ikhwanuddin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study was aimed to determine the ovarian maturation stages of wild and captive orange mud crab, Scylla olivacea fed with different diets via gonadosomatic status, oocyte diameter and histological examinations. Captive crabs were fed with blood cockle, Anadara granosa, or fish, Decapterus spp. Through the histological examinations, ovarian maturation stages of wild and captive S. olivacea was classified into four stages: Immature (Stage 1), Early maturing (Stage 2), Pre-maturing (Stage 3) and Fully matured (Stage 4). Gonadosomatic Index of wild and captive crabs remained low during immature and 2 but increased significantly (p<0.05) in pre-maturing and 4 ovaries. Oocytes size were significantly different (p<0.05) in all ovarian maturation stages of wild and captive crabs. Follicle cells surround the oocyte of immature ovary and small yolk globules start to appear in early maturing ovary with large nucleus size. Oocyte size increased significantly (p<0.05) and yolk globule obviously appeared in pre-maturing ovary. Large and fused yolk globules appeared in the oocytes of fully matured ovary with nucleus was barely visible. The present study revealed that, ovarian maturation stages of S. olivacea are closely related to its morphological appearance and cellular development.